Kontribusi Inovasi Bisnis dalam Meningkatkan Repeat Order: Studi Kasus Nelzz Juice MMTC Kota Medan - Kennedi Turnip; Anabel Yocelyn Ariella Sianturi; Hawila Manik; Jhensi Echa Flora Hutasoit; Dionisius Sihombing; Fadli Agus Triansyah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to analyze the contribution of business innovation in increasing repeat orders in micro, small, and medium enterprises (MSMEs), with a case study on Nelzz Juice operating in MMTC, Medan City. The research employs a qualitative case study approach, combining in-depth interviews with the owner and staff, direct observation of business operations, and documentation analysis related to business strategies and sales data. The findings indicate that the innovations implemented by Nelzz Juice cover several aspects, namely product innovation, service innovation, and digital marketing strategy innovation. Product innovation is carried out through the selection of fresh and high-quality ingredients, the development of creative menu variations tailored to consumer preferences, and appealing product presentation. Service innovation is reflected in the improvement of service quality, faster order processing, and enhanced friendliness and interaction with customers. Meanwhile, digital marketing innovation has proven effective in expanding consumer reach, increasing engagement, and promoting customer loyalty. The study confirms that the consistent and sustainable application of innovation not only enhances customer satisfaction but also directly contributes to an increase in repeat order frequency. Therefore, business innovation can be considered a key strategy for MSMEs to face market competition, maintain business sustainability, and support sustainable economic growth.